Karl Jaspers and the hermeneutic dichotomy between understanding and explanation in psychopathology. Could we find our feet with anyone who suffered from the Cotard syndrome type I? - Ariso, José María (Revista de Filosofía, 2012)
Though Karl Jaspers stated in his General Psychopathology that the genesis of delusions is un-understandable rational and empathically, millions of people all over the world and lots of cinema critics seem to have understood in both ways the genesis of the case of Cotard syndrome which appears by the end of the film The Sixth Sense (1999). In this paper, however, I will show that the possibility of understanding rational and empathically the genesis of this case is just unrealistic.